Time to Act: Confronting Systemic Racism in Communication Sciences and Disorders Academic Training Programs. - Ellis, Charles; Kendall, Diane (American Journal of Speech-Language Pathology, 2021)
Purpose: The intent of this tutorial is to radically shift engagement around the "types of questions" we ask around racism in communication sciences and disorders (CSD). We propose to move conversations away from diversity and inclusion and go deeper to look at the racist systems of oppression in higher education that have produced our predominantly White discipline. This low number of representations of racial minorities in CSD is extremely problematic and has deep, harmful, and far-reaching implications. The perpetuation of White production of knowledge and White culture harms minority students, faculty and clients, clinical service delivery, coursework content, and the research enterprise. Conclusions: In this tutorial, we attempt to communicate the complexity of this issue as it relates to our profession and offer ideas that at least get the discussion started. In doing so, we (a) introduce the topic in the context of the history of racism in America and how White fragility makes this topic difficult to hear, (b) provide a problem statement specific to CSD, (c) introduce the concept of systems of oppression and how this concept can change how we face racism in CSD, and (d) provide future directions.